Manifestation of polaronic effects in Josephson currents - Parafilo, A.V.; Krive, I.V.; Shekhter, R.I.; Park, Y.W.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Polaronic effects on the Josephson current through a vibrating quantum dot are considered. In the regime of strong electron–vibron interactions they lead to a power-law suppression of the critical current. This is manifestedin an anomalous temperature dependence of the critical current at temperatures of the order of the polaronic energy shift.